EFEKTIFITAS BAHASA GORONTALO DALAM PENYAMPAIAN MATERI DAKWAH - Sumarlin Adam (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2018)
The society acceptance of da’wah by using Gorontalo in the Gorontalo community looks very good, this is evidenced by the implementation and enthusiasm of the community towards the delivery of preaching messages with Gorontalo language in every activity such as the delivery of religious services at weddings, Majelis Taklim, Halal bi Halal, Maulid Nabi, Isra Miraj ‘, the attainment of lectures at the holy month of Ramadan, and lectures at ta’aziah, as well as Friday sermons. Submitting da’wah in the form of local language is a very powerful method of preaching in providing religious understanding to the community. In addition, the Gorontalo language used by the da’i is a form of maintaining regional languages.